Associations between chronotype and employment status in a longitudinal study of an elderly population. (3rd August 2022) - Didikoglu, Altug; Walker, Benjamin; Maharani, Asri; Pendleton, Neil; Canal, Maria Mercè; Payton, Antony; Gibson, Jon; Brown, Timothy
ABSTRACT: Individuals with an 'evening' chronotype tend to sleep and wake later than people described to be 'morning' type if given a free choice. Since early awakening times, due to school and occupation, may be more challenging for those with evening chronotype, they are expected to be at greater risk of adverse health, occupational and educational outcomes. Our objectives are to investigate associations between chronotype and occupational, educational and health outcomes in a longitudinal cohort. We use sleep, sociodemographic and health data from The University of Manchester Longitudinal Study of Cognition in Normal Healthy Old Age, 1982 through 2010. The relationship between employment and longitudinal midsleep trajectories were estimated using linear mixed models. Associations between employment status and Cornell Medical Index, Beck Depression Inventory scores, cortisol concentrations at different times of the day stratified by chronotype were estimated using regression. The relationship between chronotype, occupational success, education, and cognition were also examined using regression methods. In older adults, compared to non-employed participants, employed participants get up 0.45 hours earlier. Evening-type employed individuals had earlier midsleep time compared to their non-employed counterparts and had abnormal longitudinal trajectories with an increasing trend as they aged. Employed individuals with evening chronotype had a higher risk of depression than employed morning-types. Moreover, employed individuals with evening chronotype had a higher cortisol concentration at 14:00 h than non-employed individuals. In addition, memory score was lower in individuals with morning chronotype, however processing speed was higher in individuals with morning chronotype compared to evening. Morning-types had a higher age when they finished full time education. Relative to evening-types, those with morning chronotype were 6.5% more likely to be in a job classed as professional or intermediate. Our findings suggest that evening-types are at a disadvantage with regards to occupational, educational and health outcomes in older adults due to their vulnerability to circadian and sleep disruption.